The possibility of life : science, imagination, and our quest for kinship in the cosmos - Green, Jaime (Hanover Square Press, 2023)
"One of the most powerful questions humans ask about the cosmos is: Are we alone? While the science behind this inquiry is fascinating, it doesn't exist in a vacuum. It is a reflection of our values, our fears, and most importantly, our enduring sense of hope. In The Possibility of Life, acclaimed science journalist Jaime Green traces the history of our understanding, from the days of Galileo and Copernicus to our contemporary quest for exoplanets. Along the way, she interweaves insights from science fiction writers who construct worlds that in turn inspire scientists. Incorporating expert interviews, cutting-edge astronomy research, philosophical inquiry, and pop culture touchstones ranging from A Wrinkle in Time to Star Trek to Arrival, The Possibility of Life explores our evolving conception of the cosmos to ask an even deeper question: What does it mean to be human?" --